2011
DOI: 10.1097/sla.0b013e318207f39c
|View full text |Cite
|
Sign up to set email alerts
|

AmbLOXe—An Epidermal Lipoxygenase of the Mexican Axolotl in the Context of Amphibian Regeneration and Its Impact on Human Wound Closure In Vitro

Abstract: In this study, AmbLOXe, a new effector of amphibian regeneration is described. In consideration of the presented data, AmbLOXe is important for amphibian epidermal cell proliferation and migration. As AmbLOXe expressing human osteosarcoma and keratinocyte cell lines showed increased rates of in vitro wound closure, an influence of amphibian mediators on human cells could be described for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 51 publications
2
24
0
1
Order By: Relevance
“…They found that the axolotl lipoxygenase was much more efficient than human lipoxygenase in promoting wound closure in these in vitro assays. 51 This finding may not be generalized for all axolotl genes, as we have shown in a previous study that the axolotl p53 protein had no activity at 37°C in human cells. 30 However, it remains interesting that some axolotl genes known to be important for normal wound healing are more efficient in their actions than their mammalian counterparts.…”
Section: Axolotl As a Model For Scarless Wound Healingmentioning
confidence: 76%
See 1 more Smart Citation
“…They found that the axolotl lipoxygenase was much more efficient than human lipoxygenase in promoting wound closure in these in vitro assays. 51 This finding may not be generalized for all axolotl genes, as we have shown in a previous study that the axolotl p53 protein had no activity at 37°C in human cells. 30 However, it remains interesting that some axolotl genes known to be important for normal wound healing are more efficient in their actions than their mammalian counterparts.…”
Section: Axolotl As a Model For Scarless Wound Healingmentioning
confidence: 76%
“…They examined whether the epidermal lipoxygenase, a gene important for wound healing in mammals, of axolotl could influence wound closure in mammalian cells. 51 They compared the ability of axolotl versus human lipoxygenase to influence wound closure using scratch assays with different mammalian cell lines. They found that the axolotl lipoxygenase was much more efficient than human lipoxygenase in promoting wound closure in these in vitro assays.…”
Section: Axolotl As a Model For Scarless Wound Healingmentioning
confidence: 99%
“…Epithelial migration is a critical step in wound healing and regeneration. The activity of this salamander‐specific lipoxygenase on mammalian cells indicates that – in at least some circumstances – downstream responsive elements appear to be conserved among the species .…”
Section: Potentially Unique Salamander Genes With No Mammalian Ortholmentioning
confidence: 99%
“…Because of the limited experimental data on the LOX pathway of amphibians little is known about the biological function of these enzymes. Involvement of these enzymes in amphibian regeneration, wound healing [176] and oocyte maturation [177] has been suggested. 4.5.4.3.5.…”
Section: Speciesmentioning
confidence: 99%